Does macroprudential policy affect wealth inequality? Evidence from synthetic controls - Teixeira, André (Journal of Financial Stability, 2023)
This paper examines the effects of macroprudential policy (MaPP) on wealth inequality using a large dataset of 171 countries. I find that, after the adoption of MaPP, wealth concentration in the treated countries increases by 3.4 percentage points in a decade. This finding is explained by a rise in the wealth share of the top 1% combined with a sharp decline in the wealth share of the bottom 50%. These effects are stronger for prudential rules based on income, particularly in advanced economies.